Pemahaman konsep keragaman budaya Indonesia melalui auditory, intellectually, repetition (AIR) learning model pada peserta didik kelas IV sekolah dasar - Lilis Agestiyani; Sukarno Sukarno; Chumdari Chumdari (Didaktika Dwija Indria, 2023)
Abstract. This research is the action class with the purpose to increase understanding the concept of Indonesian cultural diversity with the implementation AIR learning model. In the AIR model, students work in groups. AIR learning model is Auditory, Intellectually, and Repetition. The data collection techniques make use of observation, interviews, tests, and documentation. Before applying the AIR learning model in class IV, comprehension of the concept Indonesian culture diversity the childrens was very low. it can be seen from the percentage of students completeness 15% or 17 students getting grades less than KKM. Solution to this problem is implementation of the AIR learning model two cycles. In the first cycles, this score understanding the concept of Indonesian cultural diversity increased to 45% or 9 students get a score up to KKM. And then in cycle II, it increased again to 90% or 18 students get a score up to KKM. Based on the data, it can be concluded,the application of the AIR learning model can be to increase understanding the concept of Indonesian culture diversity in the fourth grade, student of Jatipurwo elementary school II academic years 2019/2020.